Comparative Analysis of Torsional and Tensile Load Performance of Interference Screws Made of Titanium, PEEK, and PLLA: A Numerical Study - Hussain , Muzamil; Khan, Shahzad Maqsood; Shafiq, Muhammad; Abbas, Naseem; Abbas, Aqeel (The Nucleus, 2025)
Interference screws are widely used for soft tissue-to-bone or bone-to-bone graft fixation, with the choice of material being crucial for successful outcomes. This study compares the performance of interference screws made of titanium, polyetheretherketone (PEEK), and poly-L-lactic acid (PLLA) under torsional and tensile loads using a finite element model. The mechanical results showed that the mean value of the moment to failure was 15.06 Nm for titanium, 1.54 Nm for PEEK, and 0.797 Nm for PLLA. The mean load to failure of the interference screw was 6493.13 for titanium, 640.71 for PEEK, and 31.76 Nm for PLLA. The titanium exhibits the highest moment and load to failure under torsional and tensile loads. PLLA exhibits the lowest and PEEK exhibits the intermediate results. PLLA exhibits less deformation under tensile and torsional load, which makes it suitable for load-bearing applications.